Chapter 9: Defining and describing editing - Burrough-Boenisch, Joy
Supporting Research Writing explores the range of services designed to facilitate academic writing and publication in English by non-native English-speaking (NNES)authors. It analyses the realities of offering services such as education, translation, editing and writing, and then considers the challenges and benefits that result when these boundaries are consciously blurred. It thus provides an opportunity for readers to reflect on their professional roles and the services that will best serve their clients' needs. A recurring theme is, therefore, the interaction between language professional and client-author. The book offers insights into the opportunities and challenges presented by considering ourselves first and foremost as writing support professionals, differing in our primary approach (through teaching, translating, editing, writing, or a combination of those)but with a common goal. This view has major consequences for the training of professionals who support English-language publication by NNES academics and scientists. Supporting Research Writing will therefore be a stimulus to professional development for those who support English-language publication in real-life contexts and an important resource for those entering the profession.
Keywords: RESEARCH WRITING